Disbanding Prostitution Localization is Violating Female Sex Workers’ Rights: A Case of Indonesia - Rezania Dewantary, Zenny; Citra, Anathasia; Larasathy Pinkan Prameshwary, Ni Luh (Universitas Negeri Semarang (UNNES), 2023)
Many see prostitution as controversial, as it has few, if not many things to do with morality and public safety. For Indonesia in particular, such practice is also contradictory with the religious teachings upheld by the society. Realizing that the majority of people stand against prostitution practice, government authorities are competing to entirely wipe out prostitution by disbanding prostitution localizations. Total of 160 prostitution localizations had been disbanded in the span of 2016-2019. However, such attempt did not evaluate safety concerns for therein female sex workers (FSW). Prostitution will flourish, localized or not. Thus, FSW were relocating to scattered areas (increasing safety risk) or soliciting online (violating more laws). The disappearance of monitored zones for sex business will address new problems, resulted from negative effects of uncontrolled prostitution. This research is a preliminary analysis in criticizing the Indonesian government policy for disbanding prostitution localizations. Indonesia’s government promoted eradication of prostitution to conform with norms while in national level, prostitution is not entirely illegal. Sex work is not a crime and in the history, regional governments had been accommodating area for prostitution. That, in a way, provided safety for FSW from criminalization. However, a full recognition, let alone legalization, of prostitution is still far from achieved. The authors concluded that the recent prostitution localizations dissolution is a hostile attempt to eliminate the rights of FSW as women, including rights for welfare and a safe work environment. Thus, strict control for prostitution through localizations for sex work is actually the answer for a safe, monitored prostitution industry and should have not been disbanded.